Sol-gel synthesis and particle size characterization of CdSe Quantum dots - Khong, Cat Cuong (H. : ĐHQGHN, 2017)
In this article, we report on the preparation of CdSe quantum dots (QDs) by sol-gel method and their optical properties. The average size of QDs is also estimated by using various ways, such as the Scherer’s formula. The Effros-Brus-Kayanum a's theoretical expression, TEM etc. The TEM images of samples show that the mean sizes of QDs are 4 nm. The mean sizes of QDs are smaller than that of other methods and arranging from 2 to 3.6 nm.